Organizational Justice in Organizational Citizenship Behavior: A Systematic Literature Review Based on Google Scholar Data 2020-2025 - Albert Albert; Unifah Rosyidi; Kamaludin Kamaludin (FKIP - Universitas Riau, 2026)
This study aims to systematically identify, map, and analyze research trends related to Organizational Citizenship Behavior (OCB) through a Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. The study adopts a quantitative descriptive approach by reviewing peer-reviewed journal articles published between 2020 and 2025. Literature data were obtained from the Google Scholar database, and a rigorous screening process resulted in 20 selected articles that met the inclusion criteria. Bibliometric and network visualization analyses were employed to identify dominant themes and research gaps within the OCB literature. The findings reveal that while OCB has been widely studied, several important topics remain underexplored, particularly Organizational Justice, employee Performance, and Turnover Intention. Network visualization results indicate limited connectivity and research intensity in these areas compared to more established OCB themes. These findings highlight opportunities for future research to address existing gaps and deepen theoretical and empirical understanding of OCB. Overall, this study provides a comprehensive overview of current research trends and offers valuable insights for scholars seeking to develop more integrative and impactful studies in the field of education and organizational behavior.